Analysis of the effects of Suframa tax incentives on the performance of companies in the Manaus Free Zone (Research, Society and Development, 2024)
The general objective of this study is to analyze the impact of tax incentives granted by SUFRAMA on the performance of companies operating in the Manaus Free Trade Zone. And these are specific objectives: to identify which tax incentives are promoted by SUFRAMA for companies in the Manaus Industrial Pole; highlight how incentives can be instruments of economic development and their contribution to regional sustainability; and finally, discuss the performance of organizations in the face of tax incentives. The research methodology is a bibliographical study, with a qualitative approach and descriptive research. The results highlighted the importance of SUFRAMA tax incentives as catalysts for economic growth and industrial diversification in the Manaus Free Zone, emphasizing their role in attracting investments and strengthening the local business environment. These incentives not only boost the competitiveness and technological advancement of established companies, but also promote sustainability and social well-being by encouraging efficient and ecological production practices. The effectiveness of these incentives, however, varies between sectors and companies, suggesting the need for careful management to ensure that the benefits are fairly distributed and are in harmony with the region's sustainable development and social inclusion objectives. Therefore, the analysis concludes that SUFRAMA's tax incentives are fundamental to boost the economic and technological development of the Manaus Free Zone.